2023
DOI: 10.3390/ph16040580
|View full text |Cite
|
Sign up to set email alerts
|

Microorganism-Derived Molecules as Enzyme Inhibitors to Target Alzheimer’s Diseases Pathways

Abstract: Alzheimer’s disease (AD) is the most common form of dementia. It increases the risk of other serious diseases and causes a huge impact on individuals, families, and socioeconomics. AD is a complex multifactorial disease, and current pharmacological therapies are largely based on the inhibition of enzymes involved in the pathogenesis of AD. Natural enzyme inhibitors are the potential sources for targeting AD treatment and are mainly collected from plants, marine organisms, or microorganisms. In particular, micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 132 publications
(251 reference statements)
0
4
0
Order By: Relevance
“…However, it must be admitted that, based on the latest studies and the situation with the early termination of all clinical trials of the main BACE1 inhibitors such as verubecestat atabecestat, elenbecestat lanabecestat umibecestat, LY2886721, RO5508887 or PF-06751979 by pharmaceutical companies (e.g., Pfizer, AstraZeneca, Merck, Eli Lilly, Roche, Novartis, Janssen, Biogen, Amgen) due to serious side effects or actual ineffectiveness, it is possible to speculate to what extent the development of BACE inhibitors (the β-secretase inhibition hypothesis) represents a dead end, or how long the development of these inhibitors for AD treatment will continue to be preferred by pharmaceutical companies [27,45,46]. On the other hand, natural BACE1 inhibitors with different structures are still being discovered [47] and the role of the Aβ peptide is being investigated in depth [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…However, it must be admitted that, based on the latest studies and the situation with the early termination of all clinical trials of the main BACE1 inhibitors such as verubecestat atabecestat, elenbecestat lanabecestat umibecestat, LY2886721, RO5508887 or PF-06751979 by pharmaceutical companies (e.g., Pfizer, AstraZeneca, Merck, Eli Lilly, Roche, Novartis, Janssen, Biogen, Amgen) due to serious side effects or actual ineffectiveness, it is possible to speculate to what extent the development of BACE inhibitors (the β-secretase inhibition hypothesis) represents a dead end, or how long the development of these inhibitors for AD treatment will continue to be preferred by pharmaceutical companies [27,45,46]. On the other hand, natural BACE1 inhibitors with different structures are still being discovered [47] and the role of the Aβ peptide is being investigated in depth [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…The potential study of marine ecosystems may elucidate new active compounds from a wide variety of organisms and microorganisms to solve problems from Alzheimer’s disease [ 18 ] to, i.e., bacterial infections [ 19 ]. On the other hand, recent developments in proteomics approaches have shown a capacity to unravel complex biological problems.…”
Section: Resultsmentioning
confidence: 99%
“…The earliest theory proposed for Alzheimer’s disease (AD), the cholinergic hypothesis, suggested that the cause of AD is acetylcholinesterase (AChE)-induced impaired synthesis of the acetylcholine neurotransmitter. Given that, AChE inhibitors have been proven to be effective therapeutic agents for the treatment of AD . Lately, asterric acid ( 1 ), methyl asterrate ( 3 ), and ethyl asterrate ( 36 ) were explored to be AChE inhibitors.…”
Section: Bioactivities Of Asterric Acid Analogsmentioning
confidence: 99%
“…Given that, AChE inhibitors have been proven to be effective therapeutic agents for the treatment of AD. 84 Lately, asterric acid (1), methyl asterrate (3), and ethyl asterrate (36) were explored to be AChE inhibitors. Researchers supposed that the variety and size of the esterification substituent at C-2 might be critical for the AChE inhibitory activities, considering the result that the IC 50 values of 1, 3, and 36 were 66.7, 23.3, and 20.1 μM, respectively.…”
Section: Cytotoxic Activitiesmentioning
confidence: 99%